2015
DOI: 10.3892/br.2015.445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute heat stress on adrenocorticotropic hormone, cortisol, interleukin-2, interleukin-12 and apoptosis gene expression in rats

Abstract: Abstract. The aim of the present study was to investigate the effect of acute heat stress on the neuroendocrine and immunological function in rats. Male Sprague-Dawley rats were randomly divided into two groups and respectively exposed to heat (32˚C) or to room temperature (24˚C). After 7 days of heat exposure, the heat-stress rat model was established. The organ coefficients of the pituitary and adrenal glands were determined. The body temperature was measured by telemetry. The average contents of adrenocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 25 publications
(20 reference statements)
2
26
0
2
Order By: Relevance
“…In recent years, the effects of continuous high-temperature environments on animal health and well-being are gaining more attention (Maglara et al 2003;Wang et al 2015). As a source of stress, a high-temperature environment triggers a series of heat stress responses in the body.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the effects of continuous high-temperature environments on animal health and well-being are gaining more attention (Maglara et al 2003;Wang et al 2015). As a source of stress, a high-temperature environment triggers a series of heat stress responses in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Our first main finding is that the extracellular exosome present in blood and adrenal glands can be an important regulator of HS. Previous studies assessed the degree of HS in livestock based on physiological (e.g., body temperature [52], salivary or respiratory rate [53], and biochemical indicators (e.g., cortisol, adrenocorticotropic hormone, prolactin) [10,54]). However, the genetic background, HS intensity and duration can affect the stability and reliability of the response to HS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, further molecular mechanisms and physiological consequences of HS using an animal model are highly recommended.Previous studies have shown HS-induced physiological and biochemical variations in many animals, such as rats [10,11], cows [12], and chickens [13]. The HS causes an imbalance of glucocorticoids, the adrenocorticotropic hormone, the growth hormone, and the norepinephrine hormone, resulting in detrimental metabolic changes [10,14,15]. Furthermore, a set of proteins involved in the antioxidant stress response and inflammatory response, including catalase, glutathione peroxidase, and C-reactive protein were affected by HS [16][17][18][19].…”
mentioning
confidence: 99%
“…Bovine MECs (BMECs) in vitro culture are able to sense bacteria or bacterial products, and to react by upregulating the expression of several genes involved in the innate immune response (Chen et al 2014;Wang et al 2015). BMEC cultures were used as a model for udder tissue to profile the kinetics and extents of global changes in the transcriptome of BMEC after challenging them with heat-inactivated preparations of E. coli or S. aureus pathogens (Gunther et al 2011).…”
Section: Discussionmentioning
confidence: 99%